A Large-scale Search for Photometrically Variable Active Galactic Nuclei in Dwarf Galaxies Using the Young Supernova Experiment - Alexander Messick; Vivienne Baldassare; David O. Jones; K. Decker French; Sandra I. Raimundo; Nicholas Earl; Katie Auchettl; David A. Coulter; Mark E. Huber; Margaret E. Verrico; Thomas de Boer; Kenneth C. Chambers; et al. (The Astrophysical Journal)
We conduct an analysis of over 60,000 dwarf galaxies ( $7\lesssim {log}\,M_{* }/M_{\odot }\lesssim 10$ ) in search of photometric variability indicative of active galactic nuclei (AGNs). Using data from the Young Supernova Experiment, a time domain survey on the Pan-STARRS telescopes, we construct light curves for each galaxy in up to four bands ( griz ) where available. We select objects with AGN-like variability by fitting each light curve with a damped random walk (DRW) model. After quality cuts and removing transient contaminants, we identify 1100 variability-selected AGN candidates (representing 2.4% of the available sample). We analyze their spectra to measure various emission lines and calculate black hole (BH) masses, finding general agreement with previously found mass scaling relations and nine potential intermediate-mass BH candidates. Furthermore, we reanalyze the light curves of our candidates to calculate the dampening timescale τ _DRW associated with the DRW and see a similar correlation between this value and the BH mass. Finally, we estimate the active fraction as a function of stellar mass and see evidence that the active fraction increases with host mass.